PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN POTENSI AREN GUNA KONSERVASI LAHAN DAN PENINGKATAN PRODUKSI GULA AREN SEKITAR DANAU MANINJAU, NAGARI KOTO MALINTANG, SUMATERA BARAT - Anwar, Aswaldi; Wisnubroto, Muhammad Parikesit; Utami, Ami Sukma; Adrinal, Adrinal; Khairul, Ujang; Pratama, Rafdi; Adib, Muhammad; Prasetyo, Rival; Susila, Rahma; Itra, Novi Rahmat (Universitas Mataram, 2025)
The potential of aren palm (Arenga pinnata Merr.) in the area around Lake Maninjau has not been optimally utilized. Empirically, this commodity plays an important role in land conservation and improving the economy of the Nagari Koto Malintang community. Therefore, this community service activity was carried out with the aim of empowering the community to be able to manage aren trees sustainably, thereby increasing aren sugar productivity while supporting land conservation efforts in the area. This activity used methods of socialization, discussion, and direct practice with the “Kelompok Tani Hutan Gali Ide Langsung Aren) (KTH GILA), PT PLN Indonesia Power UBP Bukittinggi, and KPH Agam Raya. The results of the activity showed that the participants were enthusiastic and paid attention to the socialization and direct practice provided by the community service team. The material presented succeeded in changing the community's views and increasing their knowledge regarding palm cultivation. This change not only increased productivity and income but also raised community awareness of the importance of palm trees in preserving the environment. Overall, this community service program empowered the community through the development of palm tree potential. Through the integration of income generation and environmental conservation awareness, palm cultivation can serve as a model for sustainable economic development in Nagari Koto Malintang.